Christian apologetics : a comprehensive case for biblical faith - Groothuis, Douglas R., 1957- (Downers Grove, Ill. : IVP Academic ; Nottingham, England : Apollos, 2011)
"For millennia the Christian worldview has offered answers to our most profound and challenging questions, What gives life meaning? Is there hope? In this systematic text, Douglas Groothuis skillfully employs a cumulative case for the Christian faith, allowing several lines of argumentation and evidence to converge. This work masterfully addresses what matters most"--Provided by publisher.
Apologetic preliminaries. Introduction : hope, despair and knowing reality ; The Biblical basis for apologetics ; Apologetic method : evaluating worldviews ; The Christian worldview ; Distortions of the Christian worldview, or, The God I don't believe in ; Truth defined and defended ; Why truth matters most : searching for truth in postmodern times ; Faith, risk and rationality : the prudential incentives to Christian faith -- The case for Christian theism. In defense of theistic arguments ; The ontological argument ; The cosmological arguments : a cause for the cosmos ; The design argument : cosmic fine-tuning ; Origins, design and Darwinism ; Evidence for intelligent design ; The moral argument for God ; The argument from religious experience ; The uniqueness of humanity : consciousness and cognition ; Deposed royalty : Pascal's anthropological argument ; Jesus of Nazareth : how historians can know him and why it matters / by Craig L. Blomberg ; The claims, credentials and achievements of Jesus Christ ; Defending the Incarnation ; The Resurrection of Jesus -- Objections to Christian theism. Religious pluralism : many religions, one truth ; Apologetics and the challenge of Islam ; The problem of evil : dead ends and the Christian answer ; Conclusion : take it to the streets.
Includes bibliographical references and indexes.
Keywords: Apologetics; God (Christianity)